Pengaruh Kinerja Guru Dan Beban Kerja Terhadap Produktivitas Kerja Guru Sekolah Menengah Pertama Kecamatan Jelai Hulu - Pasaribu, Rhendivan; Wicaksono, Luhur; Zakso, Amrazi; Panggoning Salarasati, Claudi Dominico (Manajemen Pendidikan, 2025)
This study aims to obtain data and information on the significant influence of teacher performanceand workload on the work productivity of junior high school teachers in Jelai Hulu District. The formof this research uses a quantitative method with a descriptive approach. The population in this studyconsisted of 39 respondents, and the sampling method was saturated sampling, specifically targetingpublic junior high school teachers in the Jelai Hulu District, totaling 39 individuals. The respondentshad a minimum work experience of two years and were classified as Civil Servants. Among them,there were 18 male respondents aged 25-45 years and 21 female respondents aged 22-48 years. Theresearch method involved data collection using a questionnaire technique with a data collection toolin the form of a questionnaire list. The instruments developed consisted of three variables: teacherperformance, workload, and teacher work productivity. In this case, the questionnaire containingquestions will be distributed to teachers in the Jelai Hulu sub-district. The collected data will betabulated, followed by measurement using a Likert scale. The data will be analyzed using the SPSS29.00 program. Subsequently, validity, reliability, normality, linearity, and hypothesis tests will beconducted.Based on the findings and data analysis, the research concludes that:(1)Teacher performance has an influence on the work productivity of public junior high school teachersin Jelai Hulu District by 10.91%, (2) Workload has an influence on the work productivity of public juniorhigh school teachers in Jelai Hulu District by -2.34%, and teacher performance and workload togetherhave an influence on the work productivity of public junior high school teachers in Jelai Hulu Districtby 59.60%. With these findings, it can be concluded that teacher performance significantly affectsthe work productivity of teachers, and workload also has an inverse effect on the work productivity ofteachers, as indicated by the value of -23.40%. The negative value in the data obtained means that thehigher the workload, the lower the work productivity of the teachers.The implications of this researchare (1) For teachers, they should always prepare materials and lesson plans as an implementationof pedagogical skills, (2) For teachers, in accepting work burdens according to regulations, they willreceive a minimum of 24 contact hours and a maximum of 38 contact hours, so that time can be usedeffectively and efficiently, (3) For teachers and researchers, it is recommended to conduct researchwith other variables besides teacher performance and workburden.